Presidential address - Kim, Kihong (Science Editing, 2023)
I am honored to be taking on the role of the fifth President of the Korean Council of Science Editors (KCSE) for the next 3 years. The COVID-19 pandemic, which has plagued the world for the past 3 years, appears to be coming to an end. Even during the pandemic, the KCSE has persistently worked toward achieving its goal of elevating Korean science, technology, and medical journals to meet global standards by improving their editing and publishing abilities.